Expression alterations of apoptosis repressor with caspase recruitment domain in Aβ25–35-induced hippocampal neurotoxicity. Issue 1 (2nd January 2019) - Lv, Liying; Liu, Jinping; Du, Zunshu; Song, Yizhi; Li, Hui; Li, Xue; Chang, Lirong; Wu, Yan
Abstract : Many proapoptotic and antiapoptotic proteins have been involved in the pathology of Alzheimer's disease. As the first identified antiapoptotic protein, apoptosis repressor with caspase recruitment domain (ARC) is highly expressed in terminally differentiated cells, and its functions and expressions in striated muscles and cancer cells have been widely studied. However, the expression alterations of ARC in amyloid β-induced early hippocampal neurotoxicity are less known. In this report, we not only confirm previous reports that ARC is expressed in the hippocampal neurons but also demonstrate for the first time that ARC is also expressed in the hippocampal astrocytes. Furthermore, we extend the findings to show that, contrary to the time-dependently decreased ARC levels in the hippocampal neurons, ARC in astrocytes is strikingly increased in Aβ25–35 -induced early neurotoxicity. Our data suggest that ARC has distinct roles based on cell type and stimuli. Our results provide valuable information for further exploring the complicated functions and related mechanisms of ARC in amyloid-related diseases.